Pemanfaatan Tepung Maggot (Hermetia illucens) Terhadap Pertumbuhan dan Kelangsungan Hidup Udang Kaki Putih (Penaeus vannamei Boone, 1931) - Moh. Dwi Cahyadi Ardiansyah; Nasmia Nasmia; Madinawati Madinawati; Roni Hermawan (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2026)
White leg shrimp (Penaeus vannamei) is one of Indonesia's leading commodities with high economic value. The growth of white leg shrimp can be influenced by internal and external factors. Internal factors can include genetics, while external factors are dominated by feed and the environment. Feed costs in aquaculture account for 60-70% of total production costs. Raw materials that are sources of protein for shrimp feed include fishmeal, meat bone meal (MBM), poultry meat meal (PMM), and soybean meal. Maggots (Hermetia illucens) are insects that can replace imported fishmeal. Maggots contain 43.42% protein, 17.42% fat, 18.82% crude fiber, 8.70% ash, and 10.79% moisture. This study aims to determine the effect of maggot meal formulated as artificial feed on the growth performance and survival of white leg shrimp (P. vannamei). The method used is a completely randomized design (CRD) with 5 treatments and 4 replicates: (A: 0% maggot meal, B: 25% maggot meal: 75% fish meal, C: 50% maggot meal: 50% fish meal, D: 75% maggot meal: 25% fish meal, and E: 100% maggot meal). The results showed that the best utilization of maggot meal was obtained in treatment D, where the absolute weight gain (1.83 g±0.02), specific growth rate (3.90%), feed conversion ratio (3.64±0.10), and survival rate ranged from 97.5 to 100. Water quality values remained within a range suitable for white shrimp survival.